44.5k views
3 votes
Which of these equations have no solution? check all that apply

dude im dying here i need help someone help me Which of these equations have no solution? Check all that apply.

2(x + 2) + 2 = 2(x + 3) + 1
2x + 3(x + 5) = 5(x – 3)
4(x + 3) = x + 12
4 – (2x + 5) = (–4x – 2)
5(x + 4) – x = 4(x + 5) – 1

2 Answers

5 votes

Answer:

First, second and fifth

Explanation:

2(x + 2) + 2 = 2(x + 3) + 1

2x + 6 = 2x + 7

6 = 7 (false)

2x + 3(x + 5) = 5(x – 3)

5x + 15 = 5x - 15

15 = -15 (false)

4(x + 3) = x + 12

4x + 12 = x + 12

3x = 0

x = 0

4 – (2x + 5) = (–4x – 2)

4 - 2x - 10 = -4x - 2

2x = 4

x = 2

5(x + 4) – x = 4(x + 5) – 1

4x + 20 = 4x + 19

20 = 19 (false)

User Yatul
by
5.5k points
3 votes

Answer:

A, B, and E

Explanation:

Let's look through each of the answer choices.

A) 2(x + 2) + 2 = 2(x + 3) + 1

Simplify this by expanding out the parentheses:

2x + 2 * 2 + 2 = 2x + 2 * 3 + 1

2x + 4 + 2 = 2x + 6 + 1

2x + 6 = 2x + 7

6 = 7

Well, we know that 6 is NOT equal to 7, so this has no solutions.

B) 2x + 3(x + 5) = 5(x – 3)

Simplify this by expanding out the parentheses:

2x + 3x + 3 * 5 = 5x - 5 * 3

5x + 15 = 5x - 15

15 = -15

Again, we know that 15 is NOT equal to -15, so this also has no solutions.

C) 4(x + 3) = x + 12

Simplify this by expanding out the parentheses:

4x + 4 * 3 = x + 12

4x + 12 = x + 12

3x = 0

x = 0

This actually does have a solution when x = 0, so eliminate this.

D) 4 – (2x + 5) = (–4x – 2)

Simplify this by expanding out the parentheses:

4 - 2x - 5 = -4 - 2

-2x - 1 = -6

-2x = -5

x = 2.5

This also has a solution when x = 2.5, so eliminate this.

E) 5(x + 4) – x = 4(x + 5) – 1

Simplify this by expanding out the parentheses:

5x + 5 * 4 - x = 4x + 4 * 5 - 1

4x + 20 = 4x + 19

20 = 19

Here, we know that 20 is NOT equal to 19, so this has no solution.

Hope this helps!

User GregT
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.